(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Mohanty A, Acharya S, Swain BB, Mishra S, Mohapatra D, Mohapatra PK. 2023. Integrated nutrient management enhances the growth efficiency and productivity of Tagetes erecta cv. Sirakole. Asian J Agric 7: 88-97. The African marigold (Tagetes erecta L. cv. Sirakole) is a highly significant plant because it can be cultivated year-round, produce large blooms, have a long post-harvest life, and compactness. To determine the optimal fertilizer and manure combination, we conducted a study to explore the plant’s morphological, yield, and physiological characteristics under different combinations of fertilizers, Vermicompost (VC), Poultry Manure (PM), and biofertilizer (Azospirillium + phosphate solubilizing bacteria). The most successful combination for promoting vigorous growth, dense canopy, prolific branching, longer flowering duration, large-sized flowers, and higher yield was achieved with 50% Recommended Dose of Nitrogen and Phosphorus (RDNP) + VC equivalent to 25% Recommended Dose of Nitrogen (RDN) + PM equivalent to 25% RDN + biofertilizers (@400 gha-1). Additionally, plants in this combination exhibited higher chlorophyll content (Chl) and photosynthesis (PN) than those in plots with RDNP alone or other amendments. While photosynthetic fluorescence yield jP0) and energy dissipation (jD0) did not vary, plots with RDNP had lower excitation (?0) and electron movement (jE0), as well as lower photosynthesis performance indices (PIs), compared to the nutrient combinations. Additionally, the organically amended plots showed higher microbial density and soil enzyme activities than those with RDNP alone. Our findings indicate that using a combination of fertilizer, manure, and biofertilizers is the most effective way to improve the photosynthetic capacity and flower yield of T. erecta cv. Sirakole.